Effectiveness of varenicline and counselling for smoking cessation in an observational cohort study in China. Issue 1 (6th January 2016) - Jiang, Bin; He, Yao; Zuo, Fang; Wu, Lei; Liu, Qing-Hui; Zhang, Li; Zhou, Chang-Xi; Cheng, K K; Chan, Sophia S C; Lam, Tai Hing
Abstract : Objectives: To evaluate the effectiveness of varenicline for smoking cessation in Chinese smokers in a real world cessation clinic practice. Design: A prospective observational study. Setting: Beijing, China. Participants: A total of 924 smokers (883 men and 41 women) who attended a smoking cessation clinic of a large general hospital were assessed with data from structured questionnaires at baseline and follow-up at 1, 3 and 6 months. Trained physician counsellors provided free individual counselling for all subjects and follow-up interviews with brief counselling. 332 subjects additionally prescribed varenicline according to their own choice were compared with those without varenicline. Main Outcome Measures: Primary outcomes were self-reported 7-day point prevalence abstinence rate and 3-month continuous abstinence rate at 6-month follow-up. Secondary outcomes were 7-day point prevalence abstinence rates at 1 and 3-month follow-up, and 1-month continuous abstinence rate at 3-month follow-up. Results: By intention-to-treat, the 7-day point prevalence abstinence rate with varenicline and counselling at 6 months was significantly higher than counselling only (37.0% vs 23.1%; OR, 1.75; 95% CI 1.46 to 2.62; p=0.001). The 3-month continuous abstinence rate at 6 months was higher with varenicline (33.1% vs 18.4%; OR, 2.04; 95% CI 1.61 to 2.99; p<0.001). Varenicline also showed better secondary outcomes. Conclusions: Varenicline prescription in the smoking cessation clinic appeared to be effective with doubling of quit rates in Chinese smokers in a real world cessation clinic practice. Clinical trial registration: NCT01935505; Results.